O Desenho como mediador no processo de ensino e aprendizagem em Matemática - Araújo, Maria de Lourdes Haywanon Santos (2008)
This study aims at a better understanding of the role of iconographic representations to the resolution of mathematical problems. It is assumed that the act of sketching the pieces information of the problem as well as the steps of the solution facilitates a more complete learning of mathematical concepts. Iconographic representations may help in the selection between relevant and unnecessary information. However, if Expressional Sketching can play a decisive role in the learning, then, its relevance to teaching of Mathematics must be reviewed. The relationship between Expressional Sketching and Mathematics was studied with support of Vygotsky’s socio-historical approach, which made it possible to qualify the Expressional Sketching as an important symbolic mediator to visualization and graphic representation.